RTID-05. INDIGO: A GLOBAL, RANDOMIZED, DOUBLE-BLIND, PHASE 3 STUDY OF VORASIDENIB (AG-881) VS PLACEBO IN PATIENTS WITH RESIDUAL/RECURRENT GRADE II GLIOMA WITH AN ISOCITRATE DEHYDROGENASE 1/2 (IDH1/2) MUTATION. (9th November 2020) - Mellinghoff, Ingo; van den Bent, Martin; Clarke, Jennifer; Maher, Elizabeth; Peters, Katherine; Touat, Mehdi; de Groot, John; De La Fuente, Macarena; Arrillaga-Romany, Isabel; Wick, Wolfgang; Ellingson, Benjamin; Schoenfeld, Steven; et al.
Abstract: BACKGROUND: Low-grade gliomas (LGGs; WHO grade II) are incurable and ultimately progress to high-grade gliomas. The current treatment options are surgery followed by observation ("watch and wait") for patients with lower risk for disease progression or postoperative chemoradiotherapy (high-risk population). There are no approved targeted therapies. IDH1 and IDH2 mutations (m IDH1/2 ) occur in approximately 80% and 4% of LGGs, respectively, and promote tumorigenesis via neomorphic production of D-2-hydroxyglutarate. Vorasidenib, an oral, potent, reversible, brain-penetrant pan-inhibitor of mIDH1/2, was evaluated in 76 patients with glioma in two phase 1 studies (dose escalation and perioperative) and was associated with a favorable safety profile at daily doses below 100 mg. Preliminary clinical activity was observed in non-enhancing glioma patients in both studies, with an objective response rate (ORR) of 18.2% and median progression-free survival of 31.4 months in the dose escalation study. METHODS: Approximately 366 patients will be randomized 1:1 to vorasidenib (50 mg QD) or matched placebo and stratified by 1p19q status (intact vs co-deleted). Key eligibility criteria: age ≥ 12 years; grade II oligodendroglioma or astrocytoma (per WHO 2016 criteria) not in need of immediate treatment and without high-risk features; centrally confirmed m IDH1/2 status; ≥ 1 surgery for glioma with most recent ≥ 1 year but ≤ 5 years before randomization, and no other anticancer therapy; Karnofsky performance status ≥ 80%; and centrally confirmed measurable, non-enhancing disease evaluable by magnetic resonance imaging. Crossover from placebo to the vorasidenib arm is permitted upon centrally confirmed radiographic progression per RANO-LGG criteria. Primary endpoint: progression-free survival assessed by independent review. Secondary endpoints: safety and tolerability, tumor growth rate assessed by volume, ORR, overall survival, and quality of life. Clinical data will be reviewed regularly by an independent data monitoring committee. The study is currently enrolling patients in the US, with additional countries planned (NCT04164901).